Shariah Compliant Model of Currency Management: Expanding Landscape from Micro to Macro Level Research - Naqvi, Imran Muhammad Haider; Shafique, Bushra; Khan, Adeel Ahmad (European Journal of Islamic Finance, 2019)
The current interest based economic system is predominantly governed by capitalistic approach. Repetitive crisis in prevalent financial system indicated its structural flaws demanding a more viable financial system. Serendipiciously Islamic Finance (IF) appeared as a viable alternate to capitalistic system. Though IF is one of the fastest growing sectors, however, currently it is focused on microeconomic contracts between IFIs and their clients. To capitalise on the inherent strengths of IF it is needed to encompass the overall economic system in compliance with Shariah principles. Taking this into account, this qualitative and conceptual study – methodologically and substantively analyses the prevalent currency management in general and with particular reference to Pakistan for contriving its Shariah compliant mechanism. In light of Quran, Sunnah, opinions of Shariah experts it applies induction and deduction while analyzing how the prevalent currency management as per M0 is deviant from Shariah principles. Expecting good accrual of IF, it figures out the possible Shariah compliant version of M0. Subsequently our study compares the Shariah compliant version of M0 with the actual Islamic currency management model that was adopted by caliphs in ancient times. It thus contributes how to expand the horizon of Islamic finance from micro to essential macroeconomic function of currency management in an Islamic state.